Implementation of the Learning Media "Arabic Fusha" to Improve the Results of the Durūsu al-Lughah al-Arabiyah Subject at UNIDA Gontor - Fairuz Subakir; Hani'atul Mabruroh; Rizki Amalia (Alsuna: Journal of Arabic and English Language, 2022)
Purpose - This research aims to find out whether the learning media "Arabic Fusha" can help to improve the result of Durūs al-Lughah al-‘arābiyah subjects for the preparatory class at University of Darussalam Gontor. Design/methodology/approach - The study used Class Action research with two cycles. Each cycle consists of several stages: planning, execution, disinfection, and evaluation. Data collection uses observation, interview, and test methods. while data analysis uses descriptive quantitative methods. Findings/result - The result in the criteria of the class in the first cycle is 53.63%, while the result in the criteria of the class in the second cycle is 78.94%. In this case, the difference in value between the two cycles of 28.03%. This shows that the use of the learning media "Arabic Fusha" can improve the result of students in Durūs al-Lughah al-‘arābiyah material. Originality/value - Learning media "Arabic Fusha" is a media that is specially arranged for matriculation classes in the Durūs al-Lughah al-‘arābiyah subject. Paper type - Research paper